Self-harm in British South Asian women: psychosocial correlates and strategies for prevention - Husain, MI (BioMed Central, 2006)
OBJECTIVE: To review the rates of self-harm in British South Asian women, look into the factors that contribute to these high rates of self-harm and discuss possible strategies for prevention and provision of culturally sensitive service for South Asian women who harm themselves. METHOD: Review. RESULTS: South Asian women are significantly more likely to self harm between ages 16–24 years than white women. Across all age groups the rates of self harm are lower in South Asian men as compared to South Asian women. These women are generally younger, likely to be married and less likely to be unemployed or use alcohol or other drugs. They report more relationship problems within the family. South Asian women are less likely to attend the ER with repeat episode since they hold the view that mainstream services do not meet their needs. CONCLUSION: South Asian women are at an increased risk of self harm. Their demographic characteristics, precipitating factors and clinical management are different than whites. There is an urgent need for all those concerned with the mental health services for ethnic minorities to take positive action and eradicate the barriers that prevent British South Asians from seeking help. There is a need to move away from stereotypes and overgeneralisations and start from the user's frame of reference, taking into account family dynamics, belief systems and cultural constraints.